2023
DOI: 10.3390/resources12070082
|View full text |Cite
|
Sign up to set email alerts
|

New Bioretention Drainage Channel as One of the Low-Impact Development Solutions: A Case Study from Poland

Abstract: In recent years, as a result of intensive urbanisation, a significant increase in the surface of impermeable areas has been observed, which results in changes in the hydrological cycle of catchments. In order to counteract these changes, low-impact development (LID) solutions are increasingly being implemented in urban catchments, including bioretention systems. Taking this into account, a new bioretention drainage channel (BRC) was designed, whose main task is retention, infiltration, and pre-treatment of rai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…By analysing the results of the research, it was found that the pilot structures are characterised by a very high efficiency of PH removal from rainwater, close to 100%. Similar laboratory tests were conducted on two prototype rain gardens in Poland [74]. The results showed that the bioretention structure is characterised by a high efficiency of removal of PHs from rainwater, and the efficiency of the reduction in these pollutants for both prototypes is close to 100%.…”
Section: Analysis Of the Leachate From The Experimental Columnsmentioning
confidence: 79%
“…By analysing the results of the research, it was found that the pilot structures are characterised by a very high efficiency of PH removal from rainwater, close to 100%. Similar laboratory tests were conducted on two prototype rain gardens in Poland [74]. The results showed that the bioretention structure is characterised by a high efficiency of removal of PHs from rainwater, and the efficiency of the reduction in these pollutants for both prototypes is close to 100%.…”
Section: Analysis Of the Leachate From The Experimental Columnsmentioning
confidence: 79%
“…This approach also reduces the carbon footprint and, consequently, the environmental impact, enabling a more sustainable and informed use of resources. These savings are important given that reducing resource consumption at each stage of the life cycle of a device or process contributes to an overall improvement in its environmental sustainability [18,49]. Therefore, intelligent data selection and optimization of research processes are of fundamental importance for sustainable development and science, and the promotion of good practices and ecological solutions in engineering and technology.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of implementing green roofs on a building can be estimated, particularly in terms of rainwater accumulation. For comparative purposes, the runoff coefficient for green roofs was evaluated in accordance with several standards: the German standard (DIN 1986-100:2016-12 2016) [23], the Austrian standard (ÖNORM B 2501 2016) [24], the Slovak standard (STN 73 6760 2009) [25], and the FLL directive (FLL 2008) [26][27][28][29][30]. Tables 1 and 2 present the runoff coefficients as per these various standards (DIN 1986-100:2016-12 2016; ÖNORM B 2501 2016; STN 73 6760 2009; FLL 2008), contingent on the thickness of the substrate.…”
Section: Evaluation Of the Building Retention Potentialmentioning
confidence: 99%